Peran Dinas Tenaga Kerja Mandailing Natal Dalam Meningkatkan Kewirausahaan Produktif Stimulasi Ekonomi pada Masa Covid-19 - Maysaroh Hasibuan; Muhammad Arif (VISA: Journal of Vision and Ideas, 2022)
This research is expected to find out the role of Mandailing Natal Manpower Office in Improving Entrepreneurship Productive Economic Stimulation During the COVID-19 Period. The benefits of this exploration can expand information and familiarity with the region and the government in providing employment, especially during the COVID-19 period, meeting needs and expanding beneficial business ventures and financial feelings in Mandailing Natal. A subjective examination strategy which means to get the peculiarities of what the exploration subject is capable of, for example behavior, wisdom, inspiration, activity, and so on, comprehensively and expressively such as words and language, in extraordinary settings usually by using language. different. The results of the study show that the role of the Mandailing Natal Manpower Office in Increasing Economic Stimulation Productive Entrepreneurship during the COVID-19 period, really involves or fosters business visionaries who are under it with various projects that are used as a way to reduce quantity. unemployment and make serious and prevalent business people. It's just that during this COVID-19 period, the Mandailing Natal Manpower Office experienced problems, namely in persuading business people because they could not hold meetings to understand their misunderstandings with the business they were in. The progress expected by the Mandailing Natal Manpower Office or everyone else could not be felt directly or thus the Manpower Office could not immediately work on broad government assistance. Keywords: Department of Manpower, Entrepreneurship, COVID-19